Potenciální využití kalů na bázi železa pro odstraňování rizikových kovů z odpadních vod - Ulianova, Valeriia (Vysoké učení technické v Brně. Fakulta chemická, 2024)
Tato bakalářská práce se zabývá potenciálním využitím kalu na bázi železa pro odstraňování rizikových kovů z odpadních vod. Experimentální část zkoumala adsorpční schopnost aktivovaného a neaktivovaného kalu vůči olovu (Pb), niklu (Ni) a zinku (Zn). K vyhodnocení byla použita atomová absorpční spektrometrie (AAS) a analýza adsorpčních izoterm.

This bachelor's thesis deals with the potential use of iron-based sludge for the removal of heavy metals from wastewater. The experimental part investigated the adsorption capacity of activated and non-activated sludge towards lead (Pb), nickel (Ni) and zinc (Zn). Atomic absorption spectrometry (AAS) and adsorption isotherm analysis were used for evaluation.
Potential utilization of iron-based sludges for the removal of hazardous metals from wastewater
Keywords: Kal; kal na bázi železa; těžké kovy; adsorpce; odpadní voda; AAS; Sludge; iron-based sludge; heavy metals; adsorption; wastewater; AAS